Upaya Penerapan Pembelajaran Diskusi Untuk Meningkatkan Hasil Belajar Mata Pelajaran Bahasa Indonesia - Wiwik Wiji Rejeki (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2018)
The discussion method is a way of presenting lessons, where students are faced with a problem that can be a problematic statement or question to be discussed and solved together, in this discussion there is a teaching and learning process, where there are interactions between two or more individuals, involved in exchanging information to find solutions to problems and to seek truth. Learning by using discussion can improve students' learning outcomes with completeness of 61.11% to 94.44%, resulting in an increase of 33.33%. In addition, student learning activities also increased, the average overall student learning activities from 72.23% to 82.72%, resulting in an increase of 10.49%.